Expression of prostitution in the context of consumer society development - Acus, Arūnas (Social Welfare: Interdisciplinary Approach, 2012)
In this article the author analyzes the expression of the prostitution phenomenon in the context of the development of consumer society, evaluating the situation of Lithuania in 1990-2010. As prostitution is explained in various theoretical contexts, the distinct adepts of the theoretical perspectives, preserving the inner logic of arguments, represent very diverse explanations of the phenomenon of the prostitution. This article introduces the sociological discourse of the phenomenon of the prostitution; the methodological approach is supported by the theoretical insights of Davis (1994), Giddens (2005), Rubavičius (2010), Pruskus (2010), Norkus (2008). The historical evaluation of the phenomenon of the prostitution and the analysis of the development of the legal basis, which discloses the social-legal construct of the phenomenon of the prostitution in the process of the society, socio-cultural and economical development, the entrenchment arguments of the consumer society in justice are also represented in the article.
Keywords: prostitution; trafficking in human beings; procuration; consumer society